T2-Weighted Cardiac Magnetic Resonance Imaging of Edema in Myocardial Diseases. (2nd September 2012) - Amano, Yasuo; Tachi, Masaki; Tani, Hitomi; Mizuno, Kyoichi; Kobayashi, Yasuhiro; Kumita, Shinichiro
Abstract : The purpose of this paper is to describe imaging techniques and findings of T2-weighted magnetic resonance imaging (MRI) of edema in myocardial diseases. T2-weighted cardiac MRI is acquired by combining acceleration techniques with motion and signal suppression techniques. The MRI findings should be interpreted based on coronary artery supply, intramural distribution, and comparison with delayed-enhancement MRI. In acute myocardial diseases, such as acute myocardial infarction and myocarditis, the edema is larger than myocardial scarring, whereas the edema can be smaller than the scarring in some types of nonischemic cardiomyopathy, including hypertrophic cardiomyopathy. T2-weighted MRI of edema identifies myocardial edema associated with ischemia, inflammation, vasculitis, or intervention in the myocardium and provides information complementary to delayed-enhancement MRI.